ANALISIS DANA KAMPANYE LEGISLATOR PERSPEKTIF GENDER (STUDI PADA ANGGOTA DPD RI PERIODE 2019-2024) - Syamsul Arifin; Sandra Sukma Embuningtyas; Nova Sariyunita (Raheema, 2022)
This article would like to answer about how the amount of funding for elected candidates for members of the Regional Representative Council of the Republic of Indonesia (DPD RI) used for the effort to win seats is viewed from a gender perspective. This study uses a population sample technique that is all 136 DPD members representing 34 provinces in Indonesia. The type of data taken is secondary data downloaded from the General Election Comissions (KPU) official website in the form of a Report on the Acceptance and Expenditure of Campaign Funds (LPPDK). Based on the results of this study, there were three interesting things during the 2019 Concurrent Elections ago. First, the average vote acquisition of female legislators is higher than male legislators. Second, the average expenditure for women's legislator campaign funds is higher than men's legislators. Third, the average electability or costs incurred to get one vote in women legislators are cheaper than male legislators.